PERBANDINGAN PROFIL ANTIMIKROBA PADA PASIEN RAWAT INAP PNEUMONIA DI RSUD MARDI WALUYO KOTA BLITAR - Rahma, Sheilla; Laitupa, Afritra; Paramita, Ayu; Ambar, Nabil (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Pneumonia was a communicable respiratory infection associated with substantial morbidity and mortality across diverse age groups globally. Transmission occurred via direct exposure to respiratory secretions or aerosolized droplets expelled by infected individuals through coughing or sneezing. Previous investigations on antibiotic susceptibility patterns of pneumonia-causing bacterial pathogens were conducted at RSUD Dr. Soetomo Surabaya (2020) and RSUD Dr. Saiful Anwar Malang (2022). This study aimed to analyze and compare the antimicrobial susceptibility profiles of bacterial isolates from hospitalized pneumonia patients at RSUD Mardi Waluyo, Blitar City. A quantitative methodology was employed, using an observational analytic design with a cross-sectional approach to assess antibiotic resistance patterns. Statistical analysis yielded a p-value of 0.002 (p < 0.05), indicating a significant difference in antimicrobial effectiveness between Gram-positive and Gram-negative bacterial infections. The majority of patients were males over 60 years old. Staphylococcus aureus was identified as the predominant Gram-positive pathogen, while Klebsiella pneumoniae was the most prevalent Gram-negative species. Azithromycin, Erythromycin, and Levofloxacin showed the highest susceptibility among Gram-positive bacteria, whereas Amikacin, Ceftazidime, and Gentamicin were most effective against Gram-negative isolates.